Diabetes mellitus with normal renal function is associated with anaemia. Issue 4 (May 2014) - Grossman, Chagai; Dovrish, Zamir; Koren‐Morag, Nira; Bornstein, Gil; Leibowitz, Avshalom
Abstract Background Anaemia is a common complication of diabetes mellitus (DM), usually related to renal failure. There is scarce information as to the levels of haemoglobin (Hb) and the rate of anaemia in diabetic patients with normal renal function. We, therefore, evaluated haemoglobin levels and the rate of anaemia in diabetic subjects with normal renal functions [estimated glomerular filtration rate (eGFR) > 60 mL/min]. Methods The charts of 9250 subjects who attended the Institute of Periodic Medical Examinations at the Chaim Sheba Medical Center for a routine yearly check‐up were reviewed. Four hundred and forty‐five subjects with type 2 DM and normal renal function were indentified and compared with those without DM who were routinely examined at the same time. Subjects' electronic records were used to build a biochemical and clinical database. Results Mean haemoglobin levels were lower in subjects with DM than in those without (14.2 vs. 14.7 g/dL, respectively; p < 0.001). Anaemia was observed in 48 (10.8%) subjects in the diabetic group and in only 12 (2.7%) in the nondiabetic group (p < 0.001). Multivariate analysis revealed that age, gender, history of gastrointestinal disease, use of beta blockers, renal function and DM were independent determinants of haemoglobin levels. After adjustment for age, gender, history of gastrointestinal tract diseases and renal function, DM remained a significant determinant of anaemia with an odds ratio of 2.15 (confidence interval: 1.07–4.31). Conclusions Anaemia is more common in diabetic patients even when eGFR > 60 mL/min. Copyright © 2013 John Wiley & Sons, Ltd.